Egyptian-Sudanese political relations in the era of Gamal Abdel Nassr(1970-1952): Historical analytical study / Dalal Alnawari Salama Abd Karim - Dalal Alnawari Salama, Abd Karim (2016)

(untitled)
This study aims at studying the nature of relationship between Egypt and Sudan during Jamal Abdel Nasser's era. The researcher has explained that in the chapters which shed particular lighton the preparation for that relationship and revealing the historical and geographical value of the two countries. The research problem lies in analyzing the nature of the relations between Egyptian and Sudanese environmental and how did the political and historical relations between the two countries had improved and developed during Jamal Abdel Nasser's era. After that, the researcher touched on the problems that affected the nature of the relationship between the two countries in earlier periods and the way Egyptian and Sudanese managed to overcome their problems through people’s awareness of their rooted relationship and the necessity of unity based on land, neighbourhood, borders, resources and language across the history. The researcher used retrospective historical approach represented in the chapters through the limitations of the study, and thenthe analytical approach based on analysis, description and disclosing the texts. The importance of this research lies on showing the diachronic relationship between Egypt and Sudan during Nasser's era and trying to find methods to develop that relationship through raising awareness of people regarding the deeply rooted relationship between the two countries. Moreover, this research addresses the most prominent problems facing the relationship between the two countries and tries to find some solutions throughout studying their deep historical relationship between the two countries. Finally, the researcher found thatthe two countries are linked by historical and geographical ties, unified history and common destiny, while the problems took place between the two countries were due to policies, and the raised awareness of their people contributed to alleviating the crisis that was created to break the unity of Arabs and undermine their integrity.